2006
DOI: 10.1681/asn.2005111194
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Moderate to Severe Kidney Disease and Hip Fracture in the United States

Abstract: People with ESRD are at a high risk for hip fracture. However, the effect of moderate to severe chronic kidney disease (CKD) on hip fracture risk has not been well studied. As part of the Third National Health and Nutrition Examination Survey, information on both kidney function and history of hip fracture was obtained. This survey is a complex, multistage, probability sample of the US noninstitutionalized civilian population and was conducted between 1988 and 1994. A history of hip fracture was identified fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
229
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 349 publications
(243 citation statements)
references
References 37 publications
5
229
1
8
Order By: Relevance
“…Numerous studies have demonstrated increased fracture rates in adults with ESRD [8][9][10][11][12][13][14][15][16][17] and CKD. [20][21][22][23][24][25][26][27][28][29][30][31] With 90% of peak skeletal mass accrued by age 18, children with CKD are uniquely vulnerable to its multiple threats to bone health, but the The total n exceeds 67 first fracture events as there were fractures involving multiple sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated increased fracture rates in adults with ESRD [8][9][10][11][12][13][14][15][16][17] and CKD. [20][21][22][23][24][25][26][27][28][29][30][31] With 90% of peak skeletal mass accrued by age 18, children with CKD are uniquely vulnerable to its multiple threats to bone health, but the The total n exceeds 67 first fracture events as there were fractures involving multiple sites.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several studies have extended these observations to adults with moderate CKD. [20][21][22][23][24][25][26][27][28][29][30][31] Until recently, studies in children were limited to a report in solid organ transplant recipients, demonstrating a 6-fold higher incidence of all fractures and 160-fold higher incidence of vertebral fractures. 32 We subsequently completed a study in 170 children and adolescents with CKD and ESRD.…”
mentioning
confidence: 99%
“…Abnormal bone turnover occurs in approximately 85% of patients with CKD stage 5 on dialysis (CKD-5D), 2 and within this patient group, there is a greater risk of bone fracture than within the general population. [3][4][5] Although turnover abnormalities are well described, 1 little information is available on whether these abnormalities are associated with changes in bone quality. Bone quality is the contemporary term used to refer to the structural and material parameters that collectively enable bone to bear load and resist fracture or excessive deformation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Cross-sectional data suggest fracture risk increases as kidney function declines and by CKD stage 4 approximates that for ESRD. 2 Furthermore, fracture-related mortality for patients with predialysis CKD is approximately twofold higher than the general population.…”
mentioning
confidence: 99%